The five programmes of the Beethoven Quartett Society prepared and illustrated by Henry Hill, to which is prefixed a short account of that Society - Beethoven Quartett Society:::::::::::::::; Hill, Henry::::::::::::::: (London; R. Cocks & Co.; United Kingdom, 2022)
First programme: String quartets opp. 18/1, 59/3, 127 -- Second programme: String quartets opp. 18/3, 59/1, 131 -- Third programme: String quartets opp. 18/4, 74, 132 -- Fourth programme: String quartets opp. 18/2, 95, 135 -- Fifth & concluding programme: String quartets opp. 18/5, 59/2, 130. Includes program notes with printed musical incipits for each movement.